Incidence of AI in the development of soft skills in Baccalaureate students in the Dr. José María Velasco Ibarra Educational Unit - Roldán Monge, Zoila; Pérez Barrera, Hendy Maier (Revista Minerva, 2025)
The use of artificial intelligence (AI) has reached significant development, becoming a widely used tool in various areas of daily life, especially in the educational context. Students increasingly turn to AI tools as a fast-track to completing their academic assignments. While this practice can facilitate the completion of school activities, it also poses significant challenges, such as the decline in the development of soft skills essential for social interaction, such as communication, critical thinking, teamwork, and creativity. In this context, the objective of this research is to analyze the impact of AI use on the development of soft skills in high school students at the Dr. José María Velasco Ibarra Educational Unit in Ecuador. To achieve this purpose, a mixed methodological approach was employed, with an exploratory and descriptive scope, through interviews and questionnaires with a sample of 76 students. Preliminary results suggest that excessive use of AI could negatively impact the development of essential socioemotional and cognitive skills, highlighting the importance of educational strategies that integrate these tools in a balanced and formative way.